Involvement of BAG3 and HSPB7 loci in various etiologies of systolic heart failure: Results of a European collaboration assembling more than 2000 patients - Garnier S. (Elsevier Ireland Ltd, 2019)
10.1016/j.ijcard.2015.04.003